2012
DOI: 10.1074/jbc.m112.369629
|View full text |Cite
|
Sign up to set email alerts
|

TATA-binding Protein (TBP)-like Protein Is Required for p53-dependent Transcriptional Activation of Upstream Promoter of p21 Gene

Abstract: Background: TLP and p21 are involved in growth inhibition. Results: TLP decreased cell growth and activated upstream promoter of p21 gene p53-dependently. TLP bound to p53. The promoter was associated with TLP and p53, and TLP enhanced recruitment of p53 to the promoter. Conclusion: TLP is required for p53-dependent transcriptional activation of p21 upstream promoter. Significance: A novel regulator for p53-p21 pathway was identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…We have demonstrated that TLP activates several TATA-less promoters but not TATA-containing promoters [19]. Other research groups have reported the same phenomenon [37].…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…We have demonstrated that TLP activates several TATA-less promoters but not TATA-containing promoters [19]. Other research groups have reported the same phenomenon [37].…”
Section: Introductionsupporting
confidence: 74%
“…A reporter plasmid (p21up/GL4) containing an upstream region of the human p21 gene encompassing from −2266 to −1875 was described previously [19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A key target gene executing the role of p53 in cell cycle arrest is p21, which is induced by p53 through direct binding to the p21 promoter (9)(10)(11). The p21 gene is localized on chromosome 6p21.2, comprising 3 exons and 2 introns, and encodes the p21 protein.…”
Section: Introductionmentioning
confidence: 99%